Efeito da Quimiocina CXCL10 na infecção por Leishmania infantum/chagasi em camundongos BALB/C - Figueiredo, Webertty Mayk Eufrásio de (2012)
Visceral leishmaniasis caused by Leishmania infantum chagasi is characterized by the loss of the ability of host to generate an effective immune response. In this study it was investigated the role of CXCL10 chemokine in controlling L. infantum chagasi infection in vivo. Groups of BALB/c mice were treated or not with recombinant CXCL10 chemokine (5 μg/kg) with 1, 3 and 7 days of infection and after 1, 7 and 23 days of treatment, some parameters were evaluated: parasite load, levels of IFN-g, IL-4, TGF-β and IL-10, and the histopathological alterations in the liver. After 23 days of treatment, CXCL10 induced in the spleen a significant reduction on the number of parasites as compared to control group. In the liver, parasite load decreased in treated group between the 7th and 23th day post treatment. However, the antileishmanial effect of CXCL10, in this work, does not seem to be mediated by NO, since there was no difference in the NO production among the groups. IFN-γ was induced most significantly in treated group than in controls, and reached its maximum production (100 pg/mL) on day 23 after treatment, correlating with the reduction in parasite burden in target organs. IL-4 was produced in low doses, in both groups, although treated animals had shown higher levels than control group. Regarding to anti-inflammatory cytokines, after the 23th day of treatment, IL-10 levels in treated animals were smaller than in control group. Production of TGF-β after 7 days of treatment was 2 times lower in treated group when compared to control, and after the 23th day of treatment, this cytokine remained with lower levels than those observed in control. In the histopathological analysis of the liver after the 1st day of treatment, were found in both groups more immature granulomas (GI) than non-granulomatous infiltrate (NG), and some few mature granulomas (GM) were only observed in treated group. After 7 days of treatment, the amount of NG infiltrates was lower, and GI were still the most frequent in both groups, besides a slight increase of GM was observed in treated group. In summary, at the light of the found results, it is possible to suggest an important leishmanicidal role to CXCL10 in BALB/c mice infected by L. infantum chagasi, which seems to be mediated by a significant IFN-g production, and suppression of immunoregulatory cytokines, IL-10 and TGF-β, opening the hypothesis that this would be associated to a decrease in the frequency of regulatory T cells induced by CXCL10 in these animals.